Pengaruh Lingkungan Kerja dan Sarana Prasarana Terhadap Motivasi Kerja Guru di SMP Swasta Se-Kecamatan Patumbak Kabupaten Deliserdang - Netti Erni; Faisal Rahman Dongoran; Elazhari Elazhari; Masitoh Nasution; Andrison Fernando Nainggolan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of the work environment and infrastructure on the work motivation of teachers, either partially or simultaneously. This research is a quantitative research with survey method and descriptive approach and has a sample of 55 respondents. Determination of the sample using probability sampling technique with simple random sampling method. Data collection techniques were carried out by interviewing, documenting and distributing questionnaires to respondents. While the data processing technique is done by testing the validity, reliability test, data analysis prerequisite test which includes normality test, linearity test, multicollinearity test, autocorrelation test, and heteroscedasticity test, while the data analysis technique is done by correlation analysis and multiple linear regression analysis. Hypothesis testing is done by t test (partial), f test (simultaneous), and the coefficient of determination test. The results showed that: 1) the results of the t-test (partial) of the work environment variable obtained the value of tcount (3.063) > ttable (1.675) and Sig 0.000 <0.05. This shows that the work environment has a positive and significant effect on teacher work motivation; 2) the results of the t-test (partial) of the infrastructure variable obtained the value of tcount (3.550) > ttable (1.675) and Sig 0.000 <0.05. This shows that infrastructure has a positive and significant effect on teacher work motivation; 3) the results of the F test (simultaneous) obtained the value of Fcount (102.659) > Ftable (3.18) and Sig 0.000 <0.05. This shows that the work environment and infrastructure together have a positive and significant effect on teacher work motivation. Through the coefficient of determination test, the coefficient of determination is 0.798. This shows that the effect of the work environment and infrastructure together on the work motivation of teachers is 79.8% and the remaining 20.2% is influenced by other factors not included in this study. keyword: infrastructure, motivation, work environment